Down-regulation of tenascin-C inhibits breast cancer cells development by cell growth, migration, and adhesion impairment. - Dariusz Wawrzyniak (PLoS ONE, 2020)
Tenascin-C (TNC) is an extracellular matrix (ECM) glycoprotein that plays an important role in cell proliferation, migration, and tumour invasion in various cancers. TNC is one of the main protein overexpressed in breast cancer, indicating a role for this ECM molecule in cancer pathology. In this study we have evaluated the TNC loss-off-function in breast cancer cells. In our approach, we used dsRNA sharing sequence homology with TNC mRNA, called ATN-RNA. We present the data showing the effects of ATN-RNA in MDA-MB-231 cells both in monolayer and three-dimensional culture. Cells treated with ATN-RNA were analyzed for phenotypic alterations in proliferation, migration, adhesion, cell cycle, multi-caspase activation and the involvement in epithelial to mesenchymal transition (EMT) processes. As complementary analysis the oncogenomic portals were used to assess the clinical implication of TNC expression on breast cancer patient's survival, showing the TNC overexpression associated with a poor survival outcome. Our approach applied first in brain tumors and then in breast cancer cell lines reveals that ATN-RNA significantly diminishes the cell proliferation, migration and additionally, reverses the mesenchymal cells phenotype to the epithelial one. Thus, TNC could be considered as the universal target in different types of tumors, where TNC overexpression is associated with poor prognosis.